Identification of Fasciola Species Using Tegumental Spines in Tissue Sections - Arezoo FADAVI; Kayhan ASHRAFI; Hamid HASSANPOUR; Mohamad Bagher ROKNI; Seyyed Mostafa HOSSEINI; Arezoo BOZORGOMID; Leila HOSSEINPOUR; Faezeh NAJAFI; Gholamreza MOWLAVI (Tehran University of Medical Sciences, 2020)
Background: Efforts to find a reliable non-molecular means of identification has been the main purpose of the current work that always is persuaded by researchers interested in the field of parasitology. Methods: Adult fasciolids were obtained from the slaughterhouses in different parts of Iran in 2017, and investigated using the classical old fashion morphological appearances of the worms implementing a camera lucida equipped microscope. Histological procedure was subsequently performed for almost the entire collected adult worms followed by Hematoxylin and Eosin (H&E) staining technique. DNA extraction and RFLP-PCR technique were carried out for the entire fasciolid liver flukes. To attain more comparable morphological conclusions, Scanning Electron Micrographs were also implemented for two molecularly identified fasciolids.  Results: Based on spine morphology observed in worm's tissue sections two types of tegumental spines, "pointed" and "molar" shapes have been identified addressing to distinguish F. hepatica and F. gigantica species respectively. The present identification has been also supported by Molecular analysis using RFLP-PCR technique.  Conclusion: There are some hidden morphological characters implemented in species identification for certain helminths. Meanwhile, the emergence of computer image analysis system (CIAS) on the scene of taxonomy, has revolutionized the accuracy of measurement in morphology by employing detailed parameters that have not been regarded before. The current study has illustrated the tegumental spines of two Fasciola species in tissue sections which has not been enough considered in helminthological publications so far.